Tonight on the Titanic - Osborne, Mary Pope; Murdocca, Sal (New York : Random House,Scholastic, 1999)
The magic tree house transports Jack and Annie to the deck of the Titanic to find the mysterious gift that will free a small dog from a magic spell.
K
Like other books printed in this series, the Lexile number is incorrectly displayed on the back cover as 340 instead of 550.
b
b
Keywords: Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction; Shipwrecks -- Fiction; Survival -- Fiction; Time travel -- Fiction; Magic -- Fiction